2005
DOI: 10.1002/cbic.200400439
|View full text |Cite
|
Sign up to set email alerts
|

Are Hormones from the Neuropeptide Y Family Recognized by Their Receptors from the Membrane‐Bound State?

Abstract: Hormones and many other neurotransmitters, growth factors, odorant molecules, and light all present stimuli for a class of membrane-anchored receptors called G protein-coupled receptors (GPCRs). The GPCRs are the largest family of cell-surface receptors involved in signal transduction. About 1% of all known genes of Drosophila and more than 5% of the genes of Caenorhabditis elegans encode GPCRs. In addition, more than 50% of current therapeutic agents on the market target these receptors. When the enormous bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 81 publications
1
44
0
6
Order By: Relevance
“…This was in agreement with the results of another research group on NPY conformational changes with a model membrane system (dodecylphosphocholine micelle). This study revealed a raise in NPY α-helicity, particularly in its C-terminal segment upon interaction with the dodecylphosphocholine micelles 11. Given that the C-terminal of NPY is critical for binding to its targets, this conformational change favors peptide-receptor interaction 11, 20, 43, 44.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This was in agreement with the results of another research group on NPY conformational changes with a model membrane system (dodecylphosphocholine micelle). This study revealed a raise in NPY α-helicity, particularly in its C-terminal segment upon interaction with the dodecylphosphocholine micelles 11. Given that the C-terminal of NPY is critical for binding to its targets, this conformational change favors peptide-receptor interaction 11, 20, 43, 44.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the peptide has been shown to modulate oxidative fuel selection6, bone homeostasis, intestinal fluid secretion, inflammatory responses and cancer growth 610. These responses are mediated, in part, through activation of NPY/ Y (1) receptor subtype in target organs and tissues 1114. Overexpression of this receptor in malignant neoplasms was reported, particularly in breast cancer 10, 15.…”
Section: Introductionmentioning
confidence: 99%
“…56, 57 Indeed, as is known for NPY and many other peptide-GPCR systems, amphiphilic stretches along the ligand hormone serve to first anchor the peptide onto the lipid bilayer and subsequently permit activation of the membrane bound receptor. 58, 59 Thus, perhaps the present oligoclonal approach more effectively prevented ultimate signaling at the GPCR, by also interfering with appropriate peptide “recognition”, rather than by relying only on immunoneutralization of “signaling” epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the increasing angle between the NPY α-helix and the membrane surface, important membrane binding residues (L 17 /Y 20 /Y 21 ) [6] now become exposed to a rather polar environment, supported by the solution NMR data (Figure 2a). …”
mentioning
confidence: 96%